2019
DOI: 10.1021/acs.analchem.9b01027
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Test with Surface-Enhanced Raman Scattering in a Microfluidic System

Abstract: Antibiotic susceptibility test (AST) is essential in clinical diagnosis of serious bacterial infection, such as sepsis, while it typically takes 2−5 days for sample culture, antibiotic treatment, and reading result. Detecting metabolites secreted from bacteria with surface-enhanced Raman scattering (SERS) enables rapid determination of antibiotic susceptibility, reducing the AST time to 1−2 days. However, it still requires 1 day of culture time to obtain sufficient quantity of bacteria for sample washing, bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 33 publications
2
49
0
1
Order By: Relevance
“…Microuidic devices represent an alternative strategy for improving the SERS reproducibility of colloidal nanoparticles by: (1) enabling the precise control of the aggregation time using the strategy of replacing time with space; (2) reducing the mechanical and optical variations of the colloids; (3) making more efficient mixing with the analyte (automation); (4) decreasing the likely contamination (isolated systems). [75][76][77] 3.2.6 Shelf life. Another important aspect in the stability of SERS substrates lies in the shelf life, if their commercialization is desired.…”
Section: Reproducibilitymentioning
confidence: 99%
“…Microuidic devices represent an alternative strategy for improving the SERS reproducibility of colloidal nanoparticles by: (1) enabling the precise control of the aggregation time using the strategy of replacing time with space; (2) reducing the mechanical and optical variations of the colloids; (3) making more efficient mixing with the analyte (automation); (4) decreasing the likely contamination (isolated systems). [75][76][77] 3.2.6 Shelf life. Another important aspect in the stability of SERS substrates lies in the shelf life, if their commercialization is desired.…”
Section: Reproducibilitymentioning
confidence: 99%
“…[135] The application of SERS for clinical bacterial detection and identification in human body fluids has gained much attention. [136,137] In recent years, there have been a series of reports about the clinical bacterial detection and identification of SERS. For example, Avci et al analyzed and identified the pathogenic bacteria of urinary tract infection that had been cultured for 1 h by combining SERS and PCA.…”
Section: Application Of Bacterial Detection In Clinical and Food Safetymentioning
confidence: 99%
“…26 As a result, there is a huge urgency in nding rapid and costeffective assays which will have the capability for rapid and accurate determination of the appropriate antibiotic for an infection in a timely manner. [31][32][33][34][35][36][37][38][39][40][41][42] Driven by this need, the current manuscript demonstrates that 0D-2D heterostructurebased SERS is capable of rapid identication of drug resistant bacteria by monitoring structural changes in the pathogen's cell wall during antibiotic treatment. Reported data show that the SERS can be used for the identication of multidrug resistant Salmonella DT104 and a normal strain Salmonella Typhi antimicrobial susceptibility test using Augmentin antibiotics, even at the concentration of 100 CFU mL À1 experimental data reported here indicates that heterostructure-based SERS has the capability of antimicrobial susceptibility testing in less than 2 hours, whereas the "gold standard" broth microdilution (BMD) test takes 16 to 20 h in clinics until the number of bacteria reaches above 10 5 CFU mL À1 .…”
Section: Introductionmentioning
confidence: 97%